Perspectives on Practice: Building a better environment for all – an interview with Jane Daly and Siobhán Bourke - Dean, Tanya (Irish Journal of Arts Management and Cultural Policy, 2023)
In this Perspectives on Practice interview, Tanya Dean speaks to Siobhán Bourke and Jane Daly about their work with Irish Theatre Institute in supporting Irish theatre and fostering positive change in the industry. The discussion explores how the purpose of Irish Theatre Institute has evolved, and how it has adapted to and reflected the changes and challenges facing Irish theatre over the decades.